Bibliometric Mapping of Augmented Reality Research in Indonesian Senior High School - Nuzulul Ulum, M.; Gosha Patriasya, Pitra; Defriyadi (Indonesian Journal of Action Research, 2026)
Purpose – This study aims to map research trends on Augmented Reality (AR) specifically in the context of Indonesian Senior High Schools, focusing on Scopus-indexed articles that explicitly address AR implementation at the high school level in Indonesia. Methods – This study employs a bibliometric review supported by PRISMA-based document screening to ensure systematic identification and selection of relevant literature. Data were collected from the Scopus database covering publications from 2020 to 2025. From an initial 110 articles, 32 publications were selected based on predefined inclusion criteria, namely studies discussing the application of Augmented Reality in Indonesian senior high school settings. The data were analyzed using VOSviewer 1.6.20 and Microsoft Excel to examine publication trends, citation patterns, author productivity, institutional collaboration, and keyword co-occurrence. Findings – The results indicate that research on Augmented Reality in Indonesian Senior High Schools shows a fluctuating trend, with a peak in 2023. The majority of studies are concentrated in science subjects, including mathematics, physics, and biology. Keyword analysis reveals dominant themes such as augmented reality, science learning, critical thinking, and 21st-century skills, indicating a growing emphasis on innovative and competency-based learning. Collaboration among authors and institutions is increasing; however, research remains limited in non-science domains such as social sciences, languages, vocational education, and Islamic education.